Humans in the Siberian Landscapes Ethnocultural Dynamics and Interaction with Nature and Space - Bocharnikov, Vladimir N.; Steblyanskaya, Alina N. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book considers theoretical issues of the ethnocultural landscape concepts at large as well as examples of its practical application in ethnic communities of Siberia. It reveals the patterns of the processes of penetration, settlement, development and adaptation of Siberian populations from Paleolithic time to Russian colonization in the era of the Russian Empire, during Soviet modernization and in the face of modern challenges. The authors consider the principal interactions (character, stages, conditions), system-related evidence and phenomena that determine the diverse specifics and multidirectional vectors of a change in the ethnic (social, cultural, economic, legal) presence in large subregions of Siberia in the mirror of various theoretical paradigms. This transdisciplinary volume appeals to researchers, lecturers and students in the fields of geography, history, philosophy, anthropology, ecology, archaeology and interfaces to many other disciplines.
Foreword -- Preface -- Introduction -- 1 Philosophical Concepts, General Scientific Theories and Humanitarian Paradigms of Siberia Research -- 2 Siberia: A Long Way from Hunter-Gatherers and Warriors to Agrarians, Buyers and Citizens of Imperial Time -- 3. Soviet Siberia: Natural Cultural and Social Transformation and Conversion of Nature -- 4 Post-Soviet Siberia under the Conditions of National Challenges and Global Problems of the Beginning of the Third Millennium -- 5 Siberian Aborigines and Ethnic Culture: From Past to Future -- Conclusions.-Index -- Glossary. .
Keywords: Human geography; Cultural geography; Ethnology; Russia-History.; Europe, Eastern-History.; Soviet Union-History.; Geography; Social and Cultural Geography; Human Geography; Sociocultural Anthropology; Ethnography; Russian, Soviet, and East European History; Regional Geography